ParaNorman [videorecording (Blu-Ray + DVD)] - Brion, Jon (LAIKA : Shout Factory, 2012)
From the makers of Coraline comes the story of Norman, a boy who must use his ability to see and speak with the dead to save his town from a centuries-old curse. In addition to spooky zombies, he'll also have to take on mysterious ghosts, wily witches, and, worst of all, clueless grown-ups. But this young ghoul whisperer will soon find his paranormal abilities pushed to their otherworldly limits.